Construction of Vicinal Quaternary Stereogenic Centers by Enantioselective Direct Mannich‐Type Reaction Using a Chiral Bis(guanidino)iminophosphorane Catalyst. Issue 15 (8th March 2016) - Takeda, Tadahiro; Kondoh, Azusa; Terada, Masahiro
Abstract: A novel asymmetric direct Mannich‐type reaction of α‐iminophenylacetate esters with thionolactones, bearing a substituent at the α‐position, as a less acidic pronucleophile was developed. Using bis(guanidino)iminophosphorane as the chiral organosuperbase catalyst, the reaction afforded densely functionalized amino‐acid derivatives having vicinal quaternary stereogenic centers, one of which is an all‐carbon quaternary stereogenic center, in good yield with high diastereo‐ and enantioselectivities. Abstract : It's a superbase : A chiral bis(guanidino)iminophosphorane catalyzes an asymmetric direct Mannich‐type reaction of α‐iminophenylacetate esters with thionolactones, bearing a substituent at the α‐position, as a less acidic pronucleophile. The reaction affords densely functionalized amino‐acid derivatives having vicinal quaternary stereogenic centers, one of which is an all‐carbon quaternary stereogenic center, in good yield with high diastereo‐ and enantioselectivities. Bzh=benzhydryl.